If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 0.75(x + -9) = 0.5(2 + -1x) Reorder the terms: 6 + 0.75(-9 + x) = 0.5(2 + -1x) 6 + (-9 * 0.75 + x * 0.75) = 0.5(2 + -1x) 6 + (-6.75 + 0.75x) = 0.5(2 + -1x) Combine like terms: 6 + -6.75 = -0.75 -0.75 + 0.75x = 0.5(2 + -1x) -0.75 + 0.75x = (2 * 0.5 + -1x * 0.5) -0.75 + 0.75x = (1 + -0.5x) Solving -0.75 + 0.75x = 1 + -0.5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5x' to each side of the equation. -0.75 + 0.75x + 0.5x = 1 + -0.5x + 0.5x Combine like terms: 0.75x + 0.5x = 1.25x -0.75 + 1.25x = 1 + -0.5x + 0.5x Combine like terms: -0.5x + 0.5x = 0.0 -0.75 + 1.25x = 1 + 0.0 -0.75 + 1.25x = 1 Add '0.75' to each side of the equation. -0.75 + 0.75 + 1.25x = 1 + 0.75 Combine like terms: -0.75 + 0.75 = 0.00 0.00 + 1.25x = 1 + 0.75 1.25x = 1 + 0.75 Combine like terms: 1 + 0.75 = 1.75 1.25x = 1.75 Divide each side by '1.25'. x = 1.4 Simplifying x = 1.4
| -6(2x+10)=-168 | | -6(x-2)+4(3-6x)=68 | | 3(-2-3x)=-9-4 | | 12-2w=3w-8 | | 2(4+4k)+10=k | | -4(4-3x)=80 | | 8(x-3)-(x-3)=0.7 | | 2y^2-16y+32=0 | | 90+30h=126+24h | | Y(-4)+5=y | | y=5.5+x+10 | | 4.4-0.751= | | -3x-3(5x-17)=3 | | 3x^2+1=49 | | 3.25x=3000-x | | 0.5(x+1)-1=0.2 | | 5.5+x+10=0 | | t^2-15-2t=0 | | 5(7+c)=80 | | X^2-x+30=0 | | y^2-10y+21=0 | | 2x^2=-4 | | 4a=2-b | | -4n+3=1-4n | | 3(2x-5)+9=10 | | 674+69m=-380 | | 3(0)+5x=15 | | 200.00-182.51= | | b-6=4 | | 5u-5(1-u)=u+8 | | 2(0)-8x=4 | | 1+6x+7x=27 |